Oyster mushroom ethanolic extract promotes lipid accumulation and upregulates Cebpa and Slc2a4 gene expression while reducing Slc2a4 promoter methylation during 3T3-L1 adipocyte differentiation - Eko Fuji Ariyanto, Devina Nabila Fitri, Seysa Azima Arvieri, Sylvia Mahaedally, Erlina Widiarsih, Nurul Qomarilla, Nurul Setia Rahayu, Tenny Putri Wikayani, Henhen Heryaman, Afiat Berbudi, Enny Rohmawaty, Dwi Wahyudha Wira, Muhammad Hasan Bashari, Yunisa Pamela, Yuni Susanti Pratiwi, Mohammad Ghozali (Journal of Applied Pharmaceutical Science, 2025)
This study assessed the effect of an oyster mushroom ethanolic extract on lipid accumulation, Cebpa and Slc2a4 gene expression, and methylation level on Slc2a4 promoter during 3T3-L1 adipocyte differentiation. The oyster mushrooms were extracted using the maceration method with ethanol. 3T3-L1 preadipocytes were cultured and differentiated using methylisobutylxanthine, dexamethasone, and insulin cocktail-containing DMEM. Twenty-four hours after seeding, the cells were incubated with 25, 50, or 100 μg/ml of the oyster mushroom ethanolic extract for 12 days. The media were replaced every 2 days. On day 12 after differentiation induction, oil red O staining and quantitative RT-PCR were performed to analyze lipid accumulation and to measure the mRNA expression of Cebpa and Slc2a4, respectively. The methylation level on the Slc2a4 promoter was measured using pyrosequencing of bisulfite-treated DNA samples. Treatment with the oyster mushroom ethanolic extract increased the mRNA expression of Cebpa and Slc2a4 in a dose-dependent manner. The highest expression of Cebpa and Slc2a4 was observed with the addition of the 50-μg/ml oyster mushroom ethanolic extract (about two-fold and fifty-fold higher than that of the control, respectively). Moreover, lipid accumulation increased after the addition of the oyster mushroom ethanolic extract. Interestingly, the oyster mushroom ethanolic extract slightly reduced the Slc2a4 methylation level on one of the CpG sites analyzed, in a dose-dependent manner. The oyster mushroom ethanolic extract increased the lipid accumulation and the Cebpa and Slc2a4 expression, while reducing the methylation level in the Slc2a4 gene promoter region.
Keywords: 3T3-L1 cell line, Cebpa, epigenetics, oyster mushroom, Slc2a4, type 2 diabetes mellitus